The Benefits of Providing Choice in Pre Service Teacher Education - Tami B Morton; Agnes Stryker (Networks: An Online Journal for Teacher Research, 2019)
Traditionally, teacher educators provide structured lectures for their pre service teachers to impart knowledge of what will be encountered in the field once they begin teaching in schools. However, in this paper, two reading professors who are proponents of constructivist teaching, decide to provide choice in their seminars. Allowing choices provided an opportunity for students to encourage motivation, maximize performance, help increase independence and self-management skills and provide a feeling of control with their learning situation. Choices are evident in both informal and formal assignments throughout the semester. Pre service teachers who were able to share new knowledge in their self-selected forms, were able to show more critical thinking in their responses.
Keywords: pre service teachers; reading; Constructivism; choice